IMPROVING THE EFFICIENCY OF FOREIGN INVESTMENT BASED ON ENSURING THE ATTRACTIVENESS OF THE INVESTMENT ENVIRONMENT - ugli, Saminov Shokhrukh Bakhromjon (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2022)
The article examines the processes involved in attracting foreign investment to the national economy and improving ways to use them effectively. The impact of factors influencing the process of attracting and effective use of foreign investment on the efficiency of investment activity in the country was assessed. The existing shortcomings in the field of attracting and effective use of foreign investment have been identified. Scientific proposals and practical recommendations for improving the system of attracting foreign investment in the national economy have been formed.